2001
DOI: 10.1136/bjsm.35.4.274
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative heel ultrasound variables in powerlifters and controls

Abstract: Objective-To compare by cross sectional study the quantitative heel ultrasound (QUS) variables broadband ultrasound attenuation (BUA) and velocity of sound (VOS) in male powerlifters and controls. Methods-Twenty four powerlifters and 21 sedentary male controls were recruited to the study. All the powerlifters were members of the British Drug Free Powerlifting Association and actively competing at the time of the study. A questionnaire was completed by all those entered into the study. This included a history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
2
0
4
Order By: Relevance
“…Additionally, a study using DXA and QUS measurements by Lehtonen-Veromaa et al [51] showed that both femoral neck BMD and heel QUS parameters increased in the following order: control, runners, and gymnasts. In many of the studies performed, in which they have compared an athlete population and a control group, such as the case of female runners [28] or powerlifters [52], it has been observed that athletes who perform a specific sport modality in which there are both impact movements and strength exercises, the values of SOS, BUA, and Stiffness were higher than the control group. Moreover, if the values obtained in the present study of SOS, BUA, and Stiffness are compared for both the junior and senior players, the values of all three parameters are higher than those of female runners [51,53], both long and short distance [28], gymnasts [51], and powerlifters [52].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study using DXA and QUS measurements by Lehtonen-Veromaa et al [51] showed that both femoral neck BMD and heel QUS parameters increased in the following order: control, runners, and gymnasts. In many of the studies performed, in which they have compared an athlete population and a control group, such as the case of female runners [28] or powerlifters [52], it has been observed that athletes who perform a specific sport modality in which there are both impact movements and strength exercises, the values of SOS, BUA, and Stiffness were higher than the control group. Moreover, if the values obtained in the present study of SOS, BUA, and Stiffness are compared for both the junior and senior players, the values of all three parameters are higher than those of female runners [51,53], both long and short distance [28], gymnasts [51], and powerlifters [52].…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, os estudos de Garcia-Manso et al [5], Markovic et al [19] e Cleather et al [20] não foram incluídos no cálculo demonstrado acima por conter número de amostra elevado em comparação aos demais estudos analisados. Os principais instrumentos e metodologias utilizadas nos protocolos de avaliação dos atletas foram: DEXA21; Fotogrametria Digital vs Protocolo da Sociedade internacional para Avanços da Cineantropometria (iSAK)22 que incluem os valores de massa corporal, estatura, adiposidade e muscularidade através de medidas indiretas; Ultras-som [23]; Análise Alométrica (AA) [24] vs. Modelo Regressão (MR); Modelo Alométrico (MA) e Modelo de Segunda Ordem Polinominal (2OP) [25].…”
Section: Metodologiaunclassified
“…Constataram que a massa corporal era similar, com uma similaridade geométrica. Dessa forma, Jawed et al [23] identificou diferenças significativas de perfil morfofuncional em análise comparativa de sedentários e atletas de powerlifting Para estudo de Keogh et al [29], os atletas de powerlifting apresentam média de estatura de 1,75 ± 0,05 cm, com alto índice de muscularidade por cm de estatura com diferença de estaturas entre as categorias de peso moderada de 11,7 cm e a média de peso entre as categorias mais leves e mais pesadas foi identificada 34,2 kg. As diferenças na massa corporal relacionadas às medidas antropométricas dos atletas de powerlifting das categorias mais pesadas tenderam a ser significativamente maiores em valores absolutos de massa magra e adiposidade do que dos levantadores mais leves.…”
Section: Perfil Morfofisiológico Do Praticante De Powerliftingunclassified
See 2 more Smart Citations